Conocimientos, actitudes y prácticas en relación al aborto en las adolescentes del colegio Pío Jaramillo Alvarado en el periodo mayo-diciembre 2015. - Castillo Rodríguez, Alexandra Beatríz (2016)
Abortion is the termination of pregnancy before the 22 weeks of gestation, with a fetus of less than 500 gr. Teen abortion is a health problem worldwide, it is estimated that it does not decrease considering that exist methods of contraception to prevent unwanted pregnancy and abortions; for this reason was developed the study "knowledge, attitudes and practices regarding abortion in adolescents of the high school Pío Jaramillo Alvarado in the period of May / December 2015". The objectives raised of this research were: determine the knowledge that teenagers have, assess the attitudes that adolescents have and identify the number of teenagers of the high school Pío Jaramillo Alvarado who have aborted. The study was a descriptive-transversal-prospective, they were selected to students of second year of high school of the morning and evening section with a sample of 104 students (15 and 19 years old), the same who were surveyed¸ obtaining the following results: The 73% have an adequate knowledge and 27% have an inadequate knowledge on abortion; 92% won't performed an abortion for any reason, 2% do not answer and 6% has an abortion performed for the following reasons: maternal and child risk, for violation and absence of family support; 32% of adolescents have an abortion and 68% have not. It is concluded that sex education should be paramount in high school creating awareness and responsibility in adolescents and also contribute to decrease abortions. Keywords: abortion, teenagers, knowledge, attitude, practice.